At the End of the Waterfall~– Resolvability of Central Counterparties - Péter Gárdos (Credit and Capital Markets – Kredit und Kapital, 2021)
After the prudential requirements introduced by EMIR in 2012, the European Union took a further step when it adopted a regulation in 2021 on the framework for the recovery and resolution of central counterparties. The regulation is based on the bank recovery and resolution directive of 2014. This paper provides a critical overview of the new regulation by focusing on the question of whether the bank resolution tools are useful and effective in the case of central counterparty resolutions.
Keywords: K23; G23; G33; 330; central counterparties; CCP; EMIR; Dodd-Frank Ac; clearinghouses; OTC derivatives; financial market stability; recovery; resolution; resolution authority; BRRD